The Role of Parenting in Affecting the Behavior and Adaptive Functioning of Young Children of HIV-Infected Mothers in South Africa. - Allen, Alexandra Boeving; Finestone, Michelle; Eloff, Irma; Sipsma, Heather; Makin, Jennifer; Triplett, Kelli; Ebersöhn, Liesel; Sikkema, Kathleen; Briggs-Gowan, Margaret; Visser, Maretha; Ferreira, Ronél; Forsyth, Brian W C (AIDS and behavior, 2013)
Prior investigations suggest that maternal HIV/AIDS poses significant challenges to young children. This study investigates the relationships between mothers' psychological functioning, parenting, and children's behavioral outcomes and functioning in a population of women living with HIV (N = 361) with a child between the ages of 6 and 10 years in Tshwane, South Africa. Utilizing path analysis, findings revealed that maternal depression is related to increased parenting stress and parent-child dysfunction, maternal coping is related to parenting style, and maternal coping, parenting style and stress, and parent-child dysfunction are associated with children's behavior and functioning, with parenting emerging as an important mediator. These findings suggest that interventions for women living with HIV and their children should not only address maternal psychological functioning (depression and coping), but should also focus on parenting, promoting a positive approach.